Design To Build Prototype Of Atmega328 Microcontroller-Based Automatic Water Tub Filling Tool - Alexius Ulan Bani; Silvi Damayanti; Fifto Nugroho (Yayasan Bina Internusa Mabarindo, 2022)
Automatic water tank filling aims to fill tubs and torens automatically in order to save water, monitor water expenditure to be more controlled and make human work easier. the library study method collects data from sources related to the topic, hardware schematic design process and how the tool works, systematic software programs as commands for tools, tool testing implements tool work. The results of the research that made the tool work automatically well as desired, as well as stable power distribution to each sensor used.